ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEPUTIHAN DI SMK BINA JAYA PALEMBANG : Atma Deviliawati (Biro Riset, Inovasi dan Pengabdian kepada Masyarakat, Universitas Anak Bangsa, 2021)
Sexuality and reproductive health are essential aspects of an individual's personality and have a major role in determining overall health and life quality. Human reproductive system problems may affect both males and women. Vaginal discharge or fluor albus is one of the problems that may affect the female reproductive systems. Fluor albus, or vaginal discharge, is an abnormal vaginal discharge in women. According to BKKBN statistics from 2012, up to 75% of women in Indonesia have had vaginal discharge or fluor albus at least once in their lives and 45% have experienced it twice or more. According to 2012 IDHS statistics, around 18% of women aged 15-49 years have had vaginal discharge or fluor albus; the greatest rate of vaginal discharge or fluor albus occurs in unmarried women at up to 21%; and vaginal discharge or fluor albus occurs at up to 11% in women who have not graduated high school. The purpose of this research is to examine variables associated with vaginal discharge or fluor albus, including body weight, the usage of pantyliners, and special intimate organ cleansers. The research was carried out at SMK Bina Jaya Palembang on June 14 to 19 2021 with a research sample of 91 respondents who were taken by stratified random sampling. This research is an analytic observational study with a cross sectional design and tested using chi square analysis. The results showed that body weight with p value = 1,000, use of pantyliners with p value = 1,000 and special cleansers for intimate organs with p value = 1,000, indicating that there is no relationship between body weight, used of pantyliner, and special cleansers for intimate organs with vaginal discharge or fluor albus. It is advised that SMK Bina Jaya Palembang organize a consultation forum, focusing on teenage reproductive health, and include references to publications on the topic.